Implementation and performance analysis of real time PPP software based on GAMP - Liu Ya; He Wentao; Zhang Jie (Dianzi Jishu Yingyong, 2022)
Aiming at the problem that GAMP software lacks the function of real-time precise point positioning at this stage, this paper analyzes and studies the principle and process of the post precise point positioning algorithm in the software, compares the different data sources and processing methods of the real-time and post precise point positioning, and combines with the processing method of existing real-time data processing software. On the basis of GAMP, a real-time data stream receiving and preprocessing module is added. At the same time, the source of satellite precise orbit and clock bias changes from post precise ephemeris file to broadcast ephemeris combined with real-time corrections. Through the real-time precise point positioning experiment of four stations and UBLOX-F9T module, it can be found that the static real-time precision point positioning accuracy can reach centimeter level and the dynamic accuracy can reach decimeter level, which meets the needs of real-time precise point positioning.